The impact of applying the electronic declaration system on the formal tax control (Case study of tax centers in Laghouat) - Fella Mahtal; Ahmed Bessas (Dirassat Journal Economic Issue, 2020)
This study aimed to provide a theoretical framework for concepts related to electronic tax declarations, and formal tax control concepts with a focus on the most important advantages and disadvantages. The study attempted to review a set of opinions and expectations about the impact of the application of electronic tax declarations system on formal tax control, where a questionnaire was used to as a means of collecting data, and was distributed to tax executive, certified accountants and academics specialized in taxation, and after analyzing the results we concluded that by applying the electronic tax declaration system, the pros of formal tax control will be enhanced from one hand, and its disadvantages will fade away on the other hand.